PHYSICAL STUDIES OF LIGHTWEIGHT TAMPONADE COMPOSITE MATERIAL BASED ON MICROSILICA AND LOCAL ORGANOMINERAL INGREDIENTS (International journal of artificial intelligence, 2025)
The paper presents the results of selecting the composition of composite gypsum materials using inorganic fillers - ash microspheres, which are formed during the combustion of coal at thermal power plants.Based on the laboratory studies, composite compositions have been developed for obtaining thermal insulation building products with low bulk density. The rheological properties and physical and mechanical properties of mortar mixtures have been studied and the optimal compositions of composite gypsum mixtures for the production of thermal insulation materials using aluminosilicate ash microspheres have been determined.